2014
DOI: 10.1093/jac/dku091
|View full text |Cite
|
Sign up to set email alerts
|

The clinically approved drugs amiodarone, dronedarone and verapamil inhibit filovirus cell entry

Abstract: The ion channel blockers amiodarone, dronedarone and verapamil inhibit filoviral cell entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
166
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(178 citation statements)
references
References 55 publications
8
166
0
4
Order By: Relevance
“…No preclinical reports have assessed amiodarone in an animal model of filovirus infection. Amiodarone has been reported to inhibit filovirus cell entry in vitro 186 and interfere with fusion of the EBOV viral envelope with the endosomal membrane 187 .…”
Section: Buffy Coatmentioning
confidence: 99%
“…No preclinical reports have assessed amiodarone in an animal model of filovirus infection. Amiodarone has been reported to inhibit filovirus cell entry in vitro 186 and interfere with fusion of the EBOV viral envelope with the endosomal membrane 187 .…”
Section: Buffy Coatmentioning
confidence: 99%
“…Another recent study has shown three approved ion channel blockers (amiodarone, dronedarone, and verapamil) inhibited EBOV cellular entry 9 . The drugs were given at concentrations that would be achieved in human serum, and were effective against several of the filoviruses 9 . None of the FDA approved drugs described in these various studies were designed to target the Ebola virus.…”
Section: Introductionmentioning
confidence: 98%
“…We have previously summarized the numerous small molecules described in the literature as possessing antiviral activity that could be further evaluated for their potential EBOV activity alongside the few new antivirals. We have found that there is considerable prior knowledge regarding these small molecules possessing activity against EBOV in vitro or in animal models 58 , and this includes a number of accessible FDA-approved drugs 2, 3, 9 . Another recent study has shown three approved ion channel blockers (amiodarone, dronedarone, and verapamil) inhibited EBOV cellular entry 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations